THE IMPACT OF AI LITERACY ON ACCOUNTING STUDENTS' RISK MANAGEMENT ABILITY: A SYSTEMATIC LITERATURE REVIEW - Mamentu, Meike; Lumi, Vera Lionny; Najoan, Annita Patricia Carolina; Heydemans, Charnila Desria; Kaumbur, Great Erick (EDUCATIONE, 2026)
The integration of Artificial Intelligence (AI) into the accounting ecosystem demands a redefinition of professional competencies. However, empirical understanding of how AI literacy specifically shapes accounting students' risk management abilities remains limited. This study aims to analyze the impact of AI literacy on accounting students' risk management ability through a systematic literature review. The research method employed is a Systematic Literature Review (SLR) following the PRISMA protocol, focusing on 26 selected articles published between 2021 and 2025. The analysis reveals that AI literacy is a multidimensional construct encompassing technical, domain-specific (accounting), and critical-ethical aspects. Key findings indicate that AI literacy significantly contributes to enhancing risk management ability, primarily by strengthening diagnostic and prognostic capabilities. The main mechanism occurs through the process of trust calibration, where literate students can critically evaluate AI outputs, thereby assuming the role of active auditors rather than passive users. The implication of this study underscores the urgency of integrating these three dimensions of AI literacy into the core accounting curriculum to prepare adaptive and competent graduates capable of navigating risk complexity in the digital era.